Dermatitis caused by metal allergy after coil embolization for unruptured cerebral aneurysm. (3rd November 2015) - Uwatoko, Takeshi; Tsumoto, Tomoyuki; Wada, Naoko; Urabe, Kazunori; Sanbongi, Yoshiki; Tokunaga, Sou; Tsurusaki, Yuichirou; Okada, Yasushi
Abstract : We report a rare case of metal-induced dermatitis after coil embolization for cerebral aneurysm. A 51-year-old woman experienced a rash around the lips and neck 3 weeks after coil embolization. Judging from the clinical course and results of several patch tests, platinum coils were considered to have induced the dermatitis. Symptoms were relieved with administration of oral steroids. This represents the first report of metal-induced dermatitis after neuroendovascular treatment. The possibility of metal allergy was difficult to suspect preoperatively. However, early evaluation and referral are important when skin symptoms are observed postoperatively.